2001
DOI: 10.1021/es001374v
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS and XANES Studies of Copper in a Solidified Fly Ash

Abstract: Speciation of copper in the fly ash solidification process has been studied by X-ray based spectroscopies inthe present work. Fourier transformed EXAFS (extended X-ray absorption fine structural) spectra of the solidified fly ashes showed that the bond distance of Cu-O (first shell) was 1.96 A with a coordination number (CN) of about 3.0. However, in the second shell of copper atoms, the bond distance of Cu-(O)-Cu was decreased by 0.12-0.22 A during solidification, which might cause the stabilization of the Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
4
25
1
1
Order By: Relevance
“…2. The characteristic shoulder in the XANES spectra of reference compounds appear at relatively different photon energies, consistent with the observation in previous studies [9,12]. Thus it would be appropriate for the present study to compare the sample XANES spectra and their derivative curves with those of reference compounds.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2. The characteristic shoulder in the XANES spectra of reference compounds appear at relatively different photon energies, consistent with the observation in previous studies [9,12]. Thus it would be appropriate for the present study to compare the sample XANES spectra and their derivative curves with those of reference compounds.…”
Section: Resultssupporting
confidence: 88%
“…After heating, the cupric oxide became the major copper species in samples; quantification of copper species is successful due to the intrinsic simplicity of the silica matrix used. Hsiao presence of cupric hydroxide [9,10]. The copper content in the high-temperature derived fly ashes used previously is less than 0.1 wt.%.…”
Section: Introductionmentioning
confidence: 97%
“…The application of XAS to complex matrices in relation to environmental fate and behavior of contaminants is still relatively rare, but it has been employed in a limited number of studies of the speciation of metals in cement pastes, including chromium [9], cobalt [10], copper [11], lead [12], neodymium [13], selenium [14], tin [15], uranium [16] and zinc [17], as well as nickel [18][19][20]. Apart from Rinehart et al [9], who examined the oxidation state of chromium in a s/s contaminated soil and showed that this was not affected by S/S, and Hsaio et al [11], who indicated that S/S respeciated CuCl2 and reduced forms of copper in municipal waste incinerator air pollution control residues to Cu(OH)2, other studies have all prepared hydrated cement pastes by mixing pure solutions of soluble metal salts with cement powder.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Rinehart et al [9], who examined the oxidation state of chromium in a s/s contaminated soil and showed that this was not affected by S/S, and Hsaio et al [11], who indicated that S/S respeciated CuCl2 and reduced forms of copper in municipal waste incinerator air pollution control residues to Cu(OH)2, other studies have all prepared hydrated cement pastes by mixing pure solutions of soluble metal salts with cement powder. This contact mechanism is unrealistic, as contaminants in wastes are rarely fully dissolved, and the speciation observed in this way may not apply in cement-based systems containing real wastes.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of both reference materials and fly ash were measured to compare their spectral shapes and to identify the major species present. The linear combination fit (LCF) of the XANES spectra has several times been used to identify and quantify major species in particulate matter or incinerator bottom ash (Ressler et al, 2000;Hsiao et al, 2001;Takaoka et al, 2005Takaoka et al, , 2010Fujimori et al, 2010Fujimori et al, , 2011. LCF can determines the proportions of the spectra for selected standards that, when summed, yield the least fit to the spectrum of an unknown sample.…”
Section: Xanes Analysismentioning
confidence: 99%